Penerapan Metode Analytical Hierarcy Process Dalam Penentuan Penerima Bantuan Langsung Tunai COVID-19 - ,; , (Seminar Nasional Informatika (SENATIKA), 2021)
Direct Cash Assistance (BLT) is a government program due to the removal of fuel subsidies and diverted to the poor to reduce poverty in Indonesia. The existence of BLT is expected to help the prosperity of the population more evenly. So far, the selection of BLT recipient communities has been using manual methods which can slow down the work of the sub-district authorities. Often the data for the requirements was falsified and there was a lack of transparency to the public and there was an inequality of data on the provision of BLT recipients. To simplify the process of receiving BLT, an application program is needed that can help in making fast and accurate decisions. This research resulted in an application program for BLT acceptance using the AHP method. The results of this study can help the sub-district in processing BLT receipts..